2012
DOI: 10.7584/ktappi.2012.44.4.008
|View full text |Cite
|
Sign up to set email alerts
|

Application of in-situ CaCO_3 forming process on recycled fibers for optical property improvement

Abstract: Optical property improvements for ONP (old newspaper) and OMG (old magazine) were attempted by application of in-situ CaCO 3 formation process on recycled fiber surfaces. Washing treatment of ONP and OMG resulted in 35~40% yield loss for around 6% brightness improvement. Washing plus bleaching process with H 2 O 2 and FAS (formamidine sulfinic acid) improved brightness and ERIC values a little more with the same amount of yield loss as washing treatment. In-situ CaCO 3 formation method improved those optical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…[1][2][3][4][5][6] Park 등1) 은 in-situ 탄산칼슘형성 방 식을 사용하여 ONP의 수율의 감소가 없이 10-15%의 백색도 증가를 기록하였다. 1) 이러한 경우 지료의 백색도 향상은 물론이고, 유색 협잡 물들을 새로 생성되는 탄산칼슘이 감쌈으로서 ERIC (effective residual ink concentration) 값이 현저히 낮아 지는 결과를 초래하였으며, 탄산칼슘과 지료의 결합이 우수해져 초지 시 보류향상제의 첨가가 없이도 상당한 수준의 보류가 이루어짐을 보고한 바가 있다.…”
unclassified
“…[1][2][3][4][5][6] Park 등1) 은 in-situ 탄산칼슘형성 방 식을 사용하여 ONP의 수율의 감소가 없이 10-15%의 백색도 증가를 기록하였다. 1) 이러한 경우 지료의 백색도 향상은 물론이고, 유색 협잡 물들을 새로 생성되는 탄산칼슘이 감쌈으로서 ERIC (effective residual ink concentration) 값이 현저히 낮아 지는 결과를 초래하였으며, 탄산칼슘과 지료의 결합이 우수해져 초지 시 보류향상제의 첨가가 없이도 상당한 수준의 보류가 이루어짐을 보고한 바가 있다.…”
unclassified
“…They used more white ledger furnish for the printing grade paper without losing optical and strength properties by the application of the in-situ CaCO3 formation method and by controlling the refining process. Park et al (2012) and Lee et al (2013) also showed that the increase in the optical properties with a bleaching process was inferior to that of the in-situ CaCO3 formation method for ONP furnish. Actually, bleaching ONP caused a significant yield loss in the furnish.…”
Section: Introductionmentioning
confidence: 99%
“…The in-situ CaCO3 loading method on ONP improved the brightness, the effective residual ink concentration (ERIC) value, and ash retention greatly (Park et al 2012;Lee et al 2013). In this study, we investigated the mechanism responsible for the ERIC value improvement, macro sticky area changes, retention behaviors, as well as mechanical and morphological changes caused by the in-situ CaCO3 loading method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation